Hubungan Pengetahuan Gizi dengan Pola Konsumsi pada Siswa SMP dan SMA PMT Prof. Dr. Hamka II Padang - Aisyiah, Intan Kamala; Adhyka, Nurmaines; Yurizali, Bun (Jurnal Riset Hesti Medan, 2023)
Growth and development in adolescence is a crucial phase in an individual's life, with long-term impacts on health and quality of life in adulthood. Teenagers often face nutritional problems such as being overweight, underweight, and eating wrong patterns. Adolescent diet is very important in meeting nutritional needs for their growth and development. However, consumption patterns are often not by recommended nutritional standards. Nutritional knowledge plays an important role in forming a balanced consumption pattern. Although adolescents may be knowledgeable about balanced nutrition, other factors such as personal preference, the influence of friends, and the availability of less healthy foods can influence their food choices. This study aims to examine the relationship between nutritional knowledge and consumption patterns in adolescents, especially in  Prof. Dr. Hamka II Padang junior high and high school. This research method is quantitative with an analytic survey research design using a cross-sectional approach. Data were collected from 59 junior and senior high school students and analyzed using univariate analysis and bivariate analysis with the Chi-Square statistical test. The results showed that there was a significant relationship between nutritional knowledge and consumption patterns in adolescents (p=0.018). Adolescents with good nutritional knowledge tend to have better consumption patterns, while adolescents with poor nutritional knowledge tend to have poor consumption patterns. Therefore, efforts are needed to increase adolescent nutrition knowledge and provide nutrition counseling regularly. This will help them make healthier food choices and support optimal growth and development.